Improving Human Capital through Better Education to Support Indonesia's Economic Development - Adam, Latif; Negara, Siwage Dharma (Economics and Finance in Indonesia, 2015)
Despite Indonesia's impressive economic growth, it still lags behind other countries with a similar income level in terms of the quality of its human capital. This paper argues that one key factor explaining this lowÂ quality of human capital relates to the lack of focus and clear strategies to develop its education system. ThisÂ paper attempts to assess Indonesia's current state of human capital development with particular focus on it's education sector. In order to benefit from its demographic bonus, Indonesia needs to to improve its current education and skill training system. Better education and skill training system will support the country's effort to reduce poverty and youth unemployment. The effectiveness of public spending in education should be improved to raise the quality of education. Indonesia needs to integrate its human capital development plans with its economic master plan.